Stanowisko Polskiej Partii Socjalistycznej wobec zamachu majowego w 1926 roku - Kowalski, Wawrzyniec (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to present the standpoints of the Polish Socialist Party against the May coup d’Etat in 1926. The paper brings close the actual influence of socialists and dependent on trade unions within the preparation and course on the May coup d’Etat 1926. The author analyses the role and influence of the socialist past of Marshal Jozef Pilsudski in obtaining the support of the leftist forces in the decisive moments of the 1926 coup d’Etat. The article contains a comparative analysis of the political postulates of the Polish Socialist Party as well as the actions taken by the leading groupings aimed at carrying out political and system reforms in the Second Polish Republic. It was shown that the concept of Polish socialists, adopted at the beginning of the 1920s, consisting of achieving program objectives through gradual and non-revolutionary socio-political reforms, paradoxically was abandoned in 1926 in favour of solutions characteristic for revolutionary groups.
Keywords: the doctrine of Polish socialists 1918–1939; Piłsudski, Józef; Polish Socialist Party; statism; May coup d’Etat; Polish authoritarianism in the Second Polish Republic; sanation; trade unions in the Second Polish Republic in 1918–1939; parliamentarism in the Second Polish Republic